Development of electrostatic‐induced charge detector for multiturn time‐of‐flight mass spectrometer. (14th November 2022) - Bajo, Ken‐ichi; Aoki, Jun; Ishihara, Morio; Furuya, Shizuho; Nishimura, Masahiro; Yoshitake, Miwa; Yurimoto, Hisayoshi
Abstract: We developed an autocorrelation function to resolve the overtaking problem in a multiturn time‐of‐flight mass spectrometer (TOF–MS). The function analyzes the characteristic period for one lap of each ion packet and derives a mass spectrum from a signal pulse train composed of multiturn ion packets. To detect the ion pulse train, a new nondestructive ion detector was developed and installed in the multiturn orbit of MULTUM‐S II. This detector is composed of an electrostatically induced charge detector, a preamplifier, and a digitizer. The electrostatic noises are smaller than the single‐ion signals owing to the accumulation of the multiturn TOF spectrum. The conventional ion detector of TOF–MS is operated after collecting the signal pulse train. The multiturn TOF spectrum was convolved with an autocorrelation function to derive the mass spectrum. The convolved mass spectrum performed a mass resolving power (MRP) of 28, 200 at m / z 69 and mass accuracy of 28 ppm for the perfluorotributylamine (PFTBA) gas sample.